PENGEMBANGAN MEDIA WAYANG KARTUN UNTUK PEMBELAJARAN IPS DI SEKOLAH DASAR - Panggabean, Medeylin; Guslinda; Kurniaman, Otang (Jurnal Ilmiah Aquinas, 2022)
This study aims to develop cartoon puppet media for social studies learning in elementary schools and to determine the feasibility of developing cartoon puppet media. This study uses research and development methods or Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection technique used is by using a questionnaire and a limited trial. The results of the feasibility of the cartoon puppet media were obtained from the validation of experts and media trials. Validation is carried out by media experts, material experts and practitioners. The validation results show that the cartoon puppet media is very valid. Limited trials conducted on 5 students got a response that was categorized as very good. The results of this development research indicate that the cartoon puppet media is suitable for social studies learning in elementary schools. Tun, Social Studies Learning.  Keywords: Learning Media, Cartoon Puppets, Social Studies Learning